THE CONCEPT OF TOLERANCE FOR TRADITIONAL CUSTOMS IN ISLAM IN NORTH SUMATRA BUYA HAMKA'S PERSPECTIVE IN THE BOOK OF TAFSIR AL AZHAR - Muhammad Haikal Fajrin; Agusman Damanik (Journal Analytica Islamica, 2025)
This study examines how the concept of tolerance of customs in North Sumatra in the perspective of Buya Hamka in Tafsir Al Azhar. This research is a qualitative research with a literature study approach (library research) and thematic interpretation (maudhu'i). Data were collected using documentation techniques, namely through reading, recording, and reviewing texts from primary and secondary sources relevant to the focus of the research. The results of this study indicate that Tolerance is the ability to respect the basic nature, beliefs, and behavior of others because Islamic teachings do not prohibit its followers from creating and implementing a custom in dealing with something that happens to them as long as the implementation does not conflict with Islamic teachings therefore Buya Hamka emphasized that customs are part of people's lives, but must be filtered with Islamic values. In the area of North Sumatra, especially in the Javanese tribe, many of the population still follow the mutih fast. Mutih fasting is not part of Islamic teachings that are sourced from the Qur'an and Sunnah. Buya Hamka's View on the "mutihan" Label: Rejected as a tool to divide Muslims; Fasting in traditional rituals (such as mutih) is not in accordance with the Sunnah and is considered bid'ah. General Principle: All religious practices must return to the foundations of the Quran and Sunnah, without any unsubstantiated religious innovations.